Behavioural correlates of an experimental hippocampal epileptiform syndrome in rats. Issue 12 (December 1981) - Mellanby, J; Strawbridge, P; Collingridge, G I; George, G; Rands, G; Stroud, C; Thompson, P
Abstract : Experiments are reported describing assessment of abnormal behaviour of rats in which a chronic epileptiform syndrome has been induced by the injection of tetanus toxin bilaterally into their hippocampi. The abnormal behaviour included hyper-reactivity to a novel environment, intermittent aggression on handling, and abnormally passive response to a strange rat introduced into their home cage. In animals with unilateral injection of toxin, electrical records from the hippocampi have been obtained. They illustrated bilaterally simultaneous discharges and also some independence between the two hippocampi. The discharges were accompanied by overt signs of complex partial seizures during the first few weeks of the syndrome but later occurred without motor signs. In this later stage the rats were somewhat resistant to the convulsant effects of pentylenetetrazol.